As to the definition of "the right to property" as the subject of crimes against property - Олійник, П. В. (Problems of legality, 2014)
Article is devoted to establishing the scope and content of the concept of "right to property" as the subject of crimes against property under Section VI of the Special Part of the Criminal Code of Ukraine. Given the existing criminal law in science perspectives on the concept of the "right to property" as the subject of these crimes and the analysis of the provisions of the civil legislation of Ukraine provides a definition of the concept. Proposed amendments to existing criminal laws in order of de lege ferenda.